Determination of the Maximum Internal Temperature of Previously Heated Saury (Cololabis saira) Meat - Uddin, Musleh (Asian Journal of Chemistry, 2010)
Attempts have been made to assess the maximum internal temperature (MTT) of heated saury ground meat. 80 g of meat was heated at selected temperatures with different holding times. Proteins were extracted with 0.9% NaCl, then prepared a visually clear filtrate. It was possible to detect the MIT of previously heated saury meat up to 65°C by coagulation method and 70°C by SDSPAGE and DSC analysis. No coagulum was observed in filtrates prepared from 70°C heated meat and this might be due to the insufficient concentration of soluble proteins. Raw meat showed a wide variety of protein bands in SDS-PAGE with molecular weight between 19 and 53 kDa. However, only a single protein band with molecular weight of 33 kDa was detected at 65°C which could be responsible for producing coagulum at 65°C. All protein bands disappeared at 70°C. Saury raw meat had four endothermic DSC peaks. As the temperature of heat treatment increased, peaks gradually disappeared and thermogram of meat previously heated at 70°C was featureless. Results of SDS-PAGE, protein solubility, and DSC were closely related with the results of coagulation method.